(untitled) (Materiali di Estetica. Terza serie, 2024)
Lamark and Darwin, over the past centuries, have helped us to understand that the world of living, Lebenswelt, is a collection of unaccomplished. In Greek philosophy, incompleteness is the fundamental trait of everything that happens and, by happening, can be known, and distinguished, in its happening. Therefore, in every living being, to the feeling of living is added that of existing, which, on the one hand, is expressed in conflict, and on the other in love, which, as Diotima observes in the Platonic Symposium, allows every living form to tend towards eternity. In the human being, there are two forms of incompleteness: the physical one, in existence, which involves the need to reproduce in order to survive as a species, and the spiritual one, in speech, which allows another form of the ἔρως, capable of dampening conflict and creating, through the formation of political communities, human civilisations. The meaning of our history is not the prevalence of one state over another, the prevalence of the stronger over the weaker; the essence of human history is not conflict. The meaning of human history is the search for truth and beauty, the search for justice that is the good and the beautiful. In its essence, the world of life is harmony, and harmony is the essence of the plurality of human individuals and peoples, their cultures, their languages.